Bed nucleus of the stria terminalis alpha(1) and alpha(2) adrenoceptors differentially modulate the cardiovascular responses to exercise in rats - Alves, F. H. F.; Resstel, L. B. M.; Correa, F. M. A.; Crestani, Carlos Cesar [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Dynamic exercise evokes sustained blood pressure and heart rate (HR) increases. Although it is well accepted that there is a CNS mediation of cardiovascular adjustments during dynamic exercise, information on the role of specific CNS structures is still limited. The bed nucleus of the stria terminalis (BST) is involved in exercise-evoked cardiovascular responses in rats. However, the specific neurotransmitter involved in BST-related modulation of cardiovascular responses to dynamic exercise is still unclear. In the present study, we investigated the role of local BST adrenoceptors in the cardiovascular responses evoked when rats are submitted to an acute bout of exercise on a rodent treadmill. We observed that bilateral microinjection of the selective alpha 1-adrenoceptor antagonist WB4101 into the BST enhanced the HR increase evoked by dynamic exercise without affecting the mean arterial pressure (MAP) increase. Bilateral microinjection of the selective alpha 2-adrenoceptor antagonist RX821002 reduced exercise-evoked pressor response without changing the tachycardiac response. BST pretreatment with the nonselective beta-adrenoceptor antagonist propranolol did not affect exercise-related cardiovascular responses. BST treatment with either WB4101 or RX821002 did not affect motor performance in the open-field test, which indicates that effects of BST adrenoceptor antagonism in exercise-evoked cardiovascular responses were not due to changes in motor activity. The present findings are the first evidence showing the involvement of CNS adrenoceptors in cardiovascular responses during dynamic exercise. Our results indicate an inhibitory influence of BST alpha 1-adrenoceptor on the exercise-evoked HR response. Data also point to a facilitatory role played by the activation of BST alpha 2-adrenoceptor on the pressor response to dynamic exercise. (C) 2011 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: central nervous system; noradrenergic neurotransmission; adrenoceptors; dynamic exercise; treadmill; open-field test